A review of the Cautires obsoletus species group from Indo–Burma (Coleoptera: Lycidae) - Dudkova, Pavla; Bocak, Ladislav (Zootaxa, 2010)
The study deals with the net-winged beetle genus Cautires Waterhouse, 1879, which is distributed mainly in the rain forests of the Oriental region. We discuss morphology and relationships among Oriental Metriorrhynchini and we propose Bulenides Waterhouse, 1879 to be a junior subjective synonym of Cautires Waterhouse, 1879. Almost all species previously classified in Bulenides were studied, transferred to Cautires and they were placed in C. obsoletus and C. pauper groups, both proposed here. The C. obsoletus species group from Indo-Burma is reviewed and seven species, which are new to science, are described: Cautires bolavensis sp. n. (Laos), C. matsudai sp. n. (Thailand), C. kundratai sp. n. (Thailand), C. dembickyi sp. n. (India), C. hergovitsi sp. n. (Laos), C. jendeki sp. n. (Laos), and C. yunnanus sp. n. (China). These species are placed in the Cautires obsoletus group. C. testaceus (Pic, 1921) and C. regalis (Kleine, 1929) from the same region are redescribed and also placed in the C. obsoletus group. A key to the C. obsoletus species group from Indo-Burma is presented, and their distribution and biology are briefly discussed. The following new combinations are proposed for the species transferred from Bulenides and placed in the Cautires obsoletus group: Cautires adventicius (Kleine, 1926), comb. n., C. apicalis (Pic, 1925), comb. n., C. ater (Pic, 1921), comb. n., C. atropunctatus (Pic, 1925), comb. n., C. basilanus (Pic, 1925), comb. n., C. adumbratus (Kleine, 1926), comb. n., C. aterrimus (Kleine, 1926), comb. n., C. bicoloratus (Kleine, 1930), comb. n., C. coccineus (Kleine, 1930), comb. n., C. cognatus (Bourgeois, 1883), comb. n., C. corporaali (Pic, 1921), comb. n., C. duplicatus (Kleine, 1928), comb. n., C. imitator (Kleine, 1930), comb. n., C. inhumeralis (Pic, 1921), comb. n., C. javanicus (Bourgeois, 1883), comb. n., C. lineatus (Pic, 1921), comb. n., C. longissimus (Pic, 1921), comb. n., C. obsoletus (Waterhouse, 1878), comb. n., C. nebulosus (Kleine, 1930), comb. n., C. nigromaculatus (Pic, 1925), comb. n., C. pudicus (Kleine, 1931), comb. n., C. purpureus (Pic, 1922), comb. n., C. regalis (Kleine, 1929), comb. n., C. reticulatus (Kleine, 1930), comb. n., C. rianganus (Pic, 1925), comb. n., C. sijthoffi (Kleine, 1926), comb. n., C. singularithorax (Pic, 1925), comb. n., C. testaceus (Pic, 1921), comb. n., and C. triangularis (Kleine, 1930), comb. n. The following species are transferred to the Cautires pauper group: C. pauper (Waterhouse, 1878), comb. n., C. arens (Kleine, 1926), comb. n., C. argilosus (Kleine, 1926), comb. n., C. lyciformis (Kleine, 1932), comb. n., C. malayensis (Kleine, 1930), comb. n., C. nigricolor (Pic, 1925), comb. n., and C. turbidus (Waterhouse, 1878), comb. n. Several species are transferred to Cautires without an assignment to the species group: C. aridus (Kleine, 1926), comb. n., C. basalis (Pic, 1925), comb. n., C. dubius (Waterhouse, 1878), comb. n., C. flavoreticulatus (Kleine, 1932), comb. n., C. longeareolatus (Kleine, 1936), comb. n., C. papuanus (Kleine, 1935), comb. n., C. philippinensis (Kleine, 1930), comb. n., C. socius (Kleine, 1935), comb. n. Several homonyms in Cautires resulted from new combinations and new names are proposed: Cautires pseudoapicalis nom. n. (for Cautires apicalis Kleine, 1926 preoccupied by Cautires apicalis (Pic, 1925)), Cautires borneensis nom. n. (for Cautires bicoloratus Kleine, 1932 preoccupied by Cautires bicoloratus (Kleine, 1930)), Cautires sundaicus nom. n. (for Cautires javanicus Kleine, 1927 preoccupied by Cautires javanicus (Bourgeois, 1883)), Cautires fruhstorferi nom. nov. (for Cautires lineatus (Pic, 1921) preoccupied by Cautires lineatus (Hope in Gray, 1831)), Cautires slamatensis nom. nov. (for Cautires obsoletus Kleine, 1926 preoccupied by Cautires obsoletus (Waterhouse, 1878)), Cautires kinabalensis nom. nov. (for Cautires lyciformis (Kleine, 1932) preoccupied by Cautires lyciformis Pic, 1922), Cautires johannesi nom. n. (for Cautires nigricolor (Pic, 1925) preoccupied by Cautires nigricolor Pic, 1922), Cautires africanus nom. n. (for Cautires reticulatus Kleine, 1930 preoccupied by Cautires reticulatus (Kleine, 1930)), Cautires congoensis nom. n. (for Cautires triangularis Kleine, 1930 preoccupied by Cautires reticulatus (Kleine, 1930)).